MRI of cortical lesions and its use in studying their role in MS pathogenesis and disease course. (29th October 2018) - Magliozzi, R.; Reynolds, R.; Calabrese, M.
Abstract: Cortical grey matter (GM) demyelination is present from the earliest stages of multiple sclerosis (MS) and is associated with physical deficits and cognitive impairment. In particular, the rate of disability progression in MS, both in the relapsing and progressive phases, appears to be strictly associated with degenerative GM demyelination and diffuse cortical atrophy. In the last decade, several histopathological studies and advanced radiological methodologies have contributed to better identify the exact involvement/load of cortical pathology in MS, even if the specific inflammatory features and the precise cell and molecular mechanisms of GM demyelination and neurodegeneration in MS remain still not fully understood. It has been proposed that a combined neuropathology, imaging and molecular approach may help to define a more detailed characterization and precise assessment of the heterogeneous features of GM injury and inflammation in MS. This, in turn, will possibly identify specific imaging and biohumoral (cerebrospinal fluid/serum) correlates of cortical pathology that may have an important role in predicting and monitor the disease evolution.